Theoretical insights into the effect of ligands on platinum(ii) complexes with a bidentate bis(o-carborane) ligand structure. Issue 10 (1st August 2019) - Zhao, Ancong; Cai, Wanlin; Yan, Xi; Zhang, Huize; Wang, Jian; Shen, Wei
Abstract : Studying the structure–property relationship of platinum(ii ) complexes with a bidentate bis( o -carborane) ligand structure and inspiring new ideas of designing platinum(ii ) complexes. Abstract : Carboranes feature a wealth of unique structures and properties in phosphorescent transition-metal complexes (PTMCs). Herein, we identify the influence between the electronic structure in carboranes and the main ligand based on the density functional theory (DFT) and time-dependent density functional theory (TD-DFT), which affects the phosphorescence properties of carborane-containing Pt compounds. Furthermore, the mechanism, including singlet–triplet splitting energies Δ E (S n – T1 ), transition dipole moment for S0 – S n transitions, the zero-field splitting (ZFS), the radiative decay rate constant ( k r ), the Huang–Rhys factor ( S ), and the spin–orbit coupling (SOC) matrix elements 1 | H SOC |S n > have been carefully investigated. The results presented here reveal the functional action 1, 1′-bis( o -carborane) contributes to the emission process owing to the manipulation of main ligand dtb-bpy and complex 1a shows promising prospects for achieving highly efficient phosphorescence via engineering the conjugation of the main ligand dtb-bpy.